2019
DOI: 10.1007/s12529-019-09774-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a Syndemic of Psychosocial Risks During Pregnancy Using Network Analysis

Abstract: Background-Psychosocial risks during pregnancy impact maternal health in resource-limited settings, and HIV-positive women often bear a heavy burden of these factors. This study sought to use network modeling to characterize co-occurring psychosocial risks to maternal and child health among at-risk pregnant women.Methods-Two hundred pregnant HIV-positive women attending antenatal care in South Africa were enrolled. Measured risk factors included younger age, low income, low education, unemployment, unintended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 64 publications
6
20
0
Order By: Relevance
“…In a study conducted in Indonesia, young age was reported as the most dominant factor affecting prenatal distress in primigravidae. 2 According to our results, which were consistent with those in the literature, prenatal distress levels increased both in the pregnant women whose gestational age was between 12th -27th weeks, and in the pregnant women whose gestational age was between 28th -41st weeks as their age decreased [21,[30][31][32].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In a study conducted in Indonesia, young age was reported as the most dominant factor affecting prenatal distress in primigravidae. 2 According to our results, which were consistent with those in the literature, prenatal distress levels increased both in the pregnant women whose gestational age was between 12th -27th weeks, and in the pregnant women whose gestational age was between 28th -41st weeks as their age decreased [21,[30][31][32].…”
Section: Discussionsupporting
confidence: 92%
“…In a study, antenatal depression in unplanned pregnancies was reported to be signi cantly more than that in planned pregnancies [22]. Several studies conducted in different countries yielded results similar to those of the present study, and the authors of those studies showed that unplanned pregnancies in women whose gestational age was increased the distress levels [19,29,31].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Greater insight into the lived subjective experience of depression and stress, and how these are linked to SRH outcomes is needed. There appears to be a gap in the literature pertaining to the ways in which mental health and psychosocial risks, including depression and stress, intersect and overlap with SRH related factors such as distress caused by 'unintended' pregnancy, material/emotional stressors of having a child, or social stigma [16]. Various studies explore depression amongst HIV positive women, but there has been little exploration of mental health issues that arise due to, or co-occur with, SRH outcomes.…”
Section: Age and Socio-economic Related Risk Factorsmentioning
confidence: 99%